Study on the slope dynamic stability considering the progressive failure of the slip surface under earthquake - Ai, Zubin; Zhang, Huajin; Wu, Shunchuan; Jiang, Chuanbin; Yan, Qiong; Ren, Zijian (Frontiers in Earth Science, 2022)
The strength of a rock-soil mass shows complex and obvious weakening characteristics under seismic dynamic load. The previous stability analysis methods of a seismic slope do not fully depict the attenuation law of geotechnical materials and cannot truly reflect the stable state of a slope under earthquake action. Based on the theoretical analysis of the progressive failure mechanism and the evolution law of a seismic slope, the adverse effect of progressive failure on slope stability is clarified. According to the progressive failure process of a slope under dynamic load, the strain-softening model and vibration deterioration model are introduced to represent the attenuation law of rock strength parameters, and a calculation method of seismic slope stability coupled with vibration disturbance and progressive failure is proposed. The method considers the strength parameter characteristics of a rock-soil mass in different stages and is combined with the vector sum method to obtain the time-history curve of the slope safety factor under earthquake action, which makes the evaluation result of slope stability more accurate and reliable. The numerical examples show that this method can effectively reflect the dynamic stability of seismic slopes, and solve the problem that the traditional calculation methods are difficult to characterize the strength attenuation characteristics of rock and soil mass. If these characteristics are not considered, the calculation results will be unsafe.